Toothbrush Abrasion of Restorations Fabricated with Flowable Resin Composites with Different Viscosities In Vitro - Yuko Miyano (MDPI AG, 2021)
The purpose of this study was to examine toothbrush-induced abrasion of resin composite restorations fabricated with flowable resin composites of different viscosities in vitro. In this study, six types of flowable resin composites with different flowability (Beautifil Flow F02, F02; Beautifil Flow F10, F10; Beautifil Flow Plus F00, P00; Beautifil Flow Plus F03, P03; Beautifil Flow Plus X F00, X00; and Beautifil Flow Plus X F03, X03) were used. For the toothbrush abrasion test, the standard cavity (4 mm in diameter and 2 mm in depth) formed on the ceramic block was filled with each flowable resin composite (n = 10) and brushed for up to 40,000 strokes in a suspension containing commercial toothpaste under the conditions of 500 g load, 60 strokes/min, and 30 mm stroke distance. After every 10,000 strokes, the brushed surface of the specimen was impressed with a silicone rubber material. The amount of toothbrush-induced abrasion observed on each impression of the specimen was measured using a wide-area 3D measurement device (n = 10). The viscosity was determined using a cone-and-plate rotational measurement system. Because of the effect of different shear rates on viscosity and clinical use, the values 1.0 and 2.0 s−1 were adopted as data (n = 6). In this study, the results of the toothbrush abrasion test demonstrated no significant differences in the amount of toothbrush-induced abrasion among flowable resin composites used (p > 0.05). No significant correlation was reported between toothbrush-induced abrasion and viscosities of flowable resin composites.